Understanding STARA Awareness and Its Impact Among University Professors: A Qualitative Inquiry in the Nepalese Context (The Lumbini Journal of Business and Economics, 2025)
Purpose: This study aims to explore the awareness and perceptions of STARA among university professors in Nepal, focusing on how these emerging technologies may impact their professional roles and the broader university system.Methods: A qualitative research design has been employed, using semi-structured interviews to collect data from a purposive sample of 35 academics of three major universities: Tribhuvan University, Kathmandu University, and Pokhara University. Quirkos software 2.5.3 is used for thematic data analysis, allowing for an in-depth understanding of the participants’ insights.Results: The analysis reveals a complex mix of optimism, concern, and uncertainty among the professors regarding the integration of STARA into the academic sector. While some participants expressed enthusiasm about the potential benefits of STARA, such as improved efficiency and new teaching opportunities, others voiced concerns about job security, the devaluation of traditional academic roles, and the preparedness of the university system for these technological shifts.Conclusion: The study highlights the need for proactive policy-making, curriculum updates, and faculty training to address the challenges and opportunities presented by STARA in the higher education sector of Nepal. The findings underscore the importance of preparing university professors for future changes while fostering a balanced approach to integrating these technologies into academic practices.